2010
DOI: 10.1530/rep-09-0490
|View full text |Cite
|
Sign up to set email alerts
|

NME1 at the human maternal–fetal interface downregulates titin expression and invasiveness of trophoblast cells via MAPK pathway in early pregnancy

Abstract: Nometastatic gene 23-H1 (NME1, also known as nm23-H1) is a wide-spectrum tumor metastasis suppressor gene that plays an important role in suppressing the invasion and metastasis of tumor cells. It has been demonstrated that NME1 is also expressed in human firsttrimester placenta, but its function at maternal-fetal interface is not clear. The present study aimed to elucidate the biological function of NME1 at the maternal-fetal interface, especially on invasion of the human extravillous cytotrophoblasts (EVCTs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Our reanalysis showed that the level of NME1 was signi cantly lower in endometrium of endometriosis (Fig. S2E), which is in line with the previous notion that NME1 plays an important role in regulating the invasiveness of trophoblast cells and participates in the pathogenesis of endometriosis (81,82). Similarly, the level of FKBP1A is also signi cantly lower in endometrium of endometriosis (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our reanalysis showed that the level of NME1 was signi cantly lower in endometrium of endometriosis (Fig. S2E), which is in line with the previous notion that NME1 plays an important role in regulating the invasiveness of trophoblast cells and participates in the pathogenesis of endometriosis (81,82). Similarly, the level of FKBP1A is also signi cantly lower in endometrium of endometriosis (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the well-established database of membrane and secreted proteins, we predicted a variety of ligand-receptor complexes at the protein level that might be essential for conceptus-endometrium crosstalk. The predictability of our constructed interaction map was supported by a series of membrane or secreted partners that have been identi ed as key regulators of successful implantation or uterine pathology, such as calpain 2 (CAPN2) (79), integrin subunit alpha 9 (ITGA9) (47,80), and non-metastatic gene 23-H1 (NME1) (81,82). For example, membrane protein CAPN2 is highly expressed in endometrial tissues, while its interacting secreted protein cathepsin B (CTSB) is enriched in the conceptus (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The ERK1/2 signaling pathway has been reported to be involved in cell growth [ 16 ] and migration [ 23 ]. Thus, we measured TG2 and assessed whether it could modulate activation of the ERK1/2 signaling pathway in GC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Titin is a calcium-responsive protein, which is a group that is responsible for oocyte meiosis resumption [ 44 ]. Expression of titin in the human trophoblast is involved in the processes of placentation and embryo development [ 45 ]. Contactins, a subgroup of molecules belonging to the immunoglobulin superfamily, consists of six members: contactin, TAG-1, BIG-1, BIG-2, NB-2 and NB-3.…”
Section: Discussionmentioning
confidence: 99%